CLASSIFICATION OF LEAF TYPE USING ARTIFICIAL NEURAL NETWORKS - Yasar, Ali; Saritas, Ismail; Sahman, M. Akif; Dundar, A. Oktay (International Journal of Intelligent Systems and Applications in Engineering, 2015)
A number of shape features for automatic plant recognition based on digital image processing have been proposed by Pauwels et al. in 2009. Then Silva et al in 2014 have presented database comprises 40 diï¬erent plant species. We performed in our study a classification process using dataset and artificial neural networks which have been prepared by Silva and et al. It has been determined that classification accuracy is over 92%.